E-031 Superselective Intra-arterial Chemotherapy Infusion in an 8 Week-old Infant. (29th July 2016) - Sur, S; Snelling, B; Peterson, E
Abstract : Introduction: Intra-arterial chemotherapy for retinoblastoma has become standard as a therapeutic intervention to facilitate globe salvage in this aggressive malignancy. However, transfemoral endovascular catheterization of the ophthalmic artery is typically reserved for infants aged 3 months or older due to size of the patient and vascular anatomy. Here, the authors report a successful case of transfemoral intra-arterial chemotherapy delivery performed in an infant under 8 weeks of age. Case: Advanced Group E retinoblastoma was diagnosed in an otherwise healthy 8 week-old infant weighing 4.1 kg and presenting with leukocoria. A microvascular sheath (4 F, 1.3 mm outer diameter) was placed in the right common femoral artery under ultrasound guidance. A 0.014" microcatheter was inserted directly through into the sheath without use of a guide catheter and navigated over a shaped 0.008" microwire under fluoroscopy into the ostium of the right ophthalmic artery. Melphalan 1.9 mg, Topotecan 0.3 mg, and Carboplatin 30 mg were infused through the microcatheter. Results: The procedure was well tolerated and the patient was placed on weight-based lovenox for non-occlusive common femoral artery spasm diagnosed after the procedure by ultrasound. Follow-up examination under anesthesia showed good response to chemotherapy and the patient is scheduled for another session. Conclusion: The authors report successful intra-arterial delivery of chemotherapy for advanced retinoblastoma via a transfemoral approach in a small, young infant. To our knowledge, this is the youngest and smallest infant reported to have successfully undergone this procedure. While typically reserved for older and larger patients, with proper technical expertise, transfemoral intra-arterial chemotherapy can be considered in such young infants. Disclosures: S. Sur: None. B. Snelling: None. E. Peterson: None.